2020
DOI: 10.1093/neuros/nyaa441
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of the Timed Up and Go Test as Measure of Objective Functional Impairment in Patients With Lumbar Degenerative Disc Disease

Abstract: BACKGROUND The Timed Up and Go (TUG) test is the most commonly applied objective measure of functional impairment in patients with lumbar degenerative disc disease (DDD). OBJECTIVE To demonstrate external content validity of the TUG test. METHODS Consecutive adult patients, scheduled for elective lumbar spine surgery, were screened for enrollment into a prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…Overall, the results showed a moderate inverse correlation of changes in walking distances (6WD and DTFS) to subjective measures, indicating that patients with more pain and/or disability walked shorter distances without relevant symptoms. In line with our findings, previous studies have shown a weak to moderate correlation of different objective outcome measures, like the timed up-and-go (TUG) test or the motorized treadmill test (MTT), with PROMs [20,21]. Subjective and objective assessments in lumbar DLD patients do not seem to always align in a linear fashion, indicating that the 6WT is not a mere objectification of PROM questionnaires and should be considered a separate dimension in the outcome assessment of spine patients [6].…”
Section: Reliability and Validitysupporting
confidence: 92%
“…Overall, the results showed a moderate inverse correlation of changes in walking distances (6WD and DTFS) to subjective measures, indicating that patients with more pain and/or disability walked shorter distances without relevant symptoms. In line with our findings, previous studies have shown a weak to moderate correlation of different objective outcome measures, like the timed up-and-go (TUG) test or the motorized treadmill test (MTT), with PROMs [20,21]. Subjective and objective assessments in lumbar DLD patients do not seem to always align in a linear fashion, indicating that the 6WT is not a mere objectification of PROM questionnaires and should be considered a separate dimension in the outcome assessment of spine patients [6].…”
Section: Reliability and Validitysupporting
confidence: 92%
“…The increasing use of the TUG test as an objective measure of function in published articles points to its value as a brief functional test in patients with lumbar DDD 1,7,22,23 Previous reports have demonstrated the TUG test's excellent intra-rater (97%) and inter-rater reliability (99%) with a low error of measurement in different patient populations. 12,13 Since its introduction in the late 80 s by Jaeschke et al, the concept of MCID has become a cornerstone in the evaluation of the psychometric properties of an outcome measurement in spine surgery. 24 This is true both for PROMs as well as for objective measures of function, where it is crucial to determine that a specific change in OFI can be considered as clinically meaningful with confidence.…”
Section: Discussionmentioning
confidence: 99%
“…NYHA III, lung cancer, and diffuse parenchymal lung disease) or other medical reasons interfering with the patient's ability to walk and perform the TUG test. 13 A patient flow chart is depicted in Supplemental Figure 1, http://links.lww.com/BRS/B777. According to the original study by Gautschi et al, all assessments were conducted before, usually on the day before the scheduled surgery, and around 6 weeks postoperative (W6).…”
Section: Methods Patient Identification and Inclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…69 It has been used in several populations with and without disabilities. [70][71][72][73][74] Reference values vary from age groups and populations, 75,76 however, robust data on long COVID patients hospitalized due to moderate or severe COVID-19 is still limited in the literature.…”
Section: Discussionmentioning
confidence: 99%